Treatment of a smoker with an obsessive compulsive disorder of personality - López Durán, Ana; Fernández del Río, Elena; Becoña Iglesias, Elisardo (Anales de Psicología / Annals of Psychology, 2010)
The relationship between personality disorders and drug con- sumption has charged a growing interest in the last years for the difficul- ties in the treatment. But the relationship between personality disorders and smoking cessation are an aspect fewer analyzed, because there are few studies about it. The aim of this study is to analyze the assessment, treat- ment and follow-ups of a subject with an obsessive-compulsive personal- ity disorder. He received psychological treatment to quit smoke. The result of this treatment shows that the presence of a personality disorder is not always a factor that difficult the smoking cessation.